The new factors defining variability of circadian’s rhythms of intraocular and perfusion pressure of glaucoma patients - N. A. Baranova; A. V. Kuroyedov; Yu. V. Ovchinnikov (Oftalʹmologiâ)
Currently, the most scientifically based local risk and progressive factors are elevated levels of intraocular pressure and its instability during the day, caused by local hydromechanical disturbances. However, the other factors affecting the circadian changes of intraocular pressure levels are still evaluated. It was found that light is one of the most important factors affecting the intensity of the cyclical fluctuations of various biological processes, including, and fluctuations of intraocular pressure. At the same time, glaucoma can lead to a variety of sleep disorders, due to a mismatch between cycles «sleep-wake». One if this reason is the death of retinal ganglion cells and their axons. Such damage indirectly lead to a decrease in production of the pigment melanopsin, which is located in the retina. It is not involved in the visual process, but ensures the implementation of circadian rhythms «sleep-wake» and mediated suppression of epiphyseal melatonin. Most likely, melatonin plays a protective role in the occurrence and progression of glaucoma, protecting retinal cells against free radicals and has a direct impact on the intraocular pressure level. Several studies have shown that the circadian change in intraocular pressure levels, and in particular, its substantial reduction, is influenced by melatonin. In this regard, glaucoma is a disease in which the death of retinal cells, including producing melanopsin, a unique opportunity to study violations of cyclic rhythms. Melatonin acts on such established risk factors and progression of glaucoma as hypertension and diabetes. There are published results of the use of melatonin agonists in the experiment and clinical practice. So, in addition to local and systemic hypotensive action, normalizes sleep patients. Data about the melatonin’s effects on the direct and indirect reduction of intraocular pressure, neuroprotective effects and reducing symptoms of depression can be used in the complex treatment of patients with glaucoma in future.